Índices de calidad de agua en México y Colombia. Evolución, criterios y cambios (2022)
The Water Quality Index (WQI) is a simple and easy-to-understand tool for analyzing and reporting quality trends. Water quality is not static and depends on multiple factors, in this sense; globally various indices have been developed based on local water quality criteria. This paper explores and discusses about water quality assessment and their steps taking into account the widely used index models in the world. These steps include selecting the parameters, sub-index generation, weightings of the parameters, and sub-indices aggregation. The advantages and disadvantages of each index identified,and the main limitations that arise in the calculation of the different methodologies detected. These limitations are the subjectivity in selecting and weighing the parameters and the ambiguity and eclipsing in the aggregation stage. Objectivemethodological tools to solve these limitations consider the use of statistical and fuzzy logic techniques. The CCMEWQI is a versatile water quality index, since it allows the determination of the temporal and spatial conditions for the different uses in a specific way, achieving with regulations, and based on the analysis of monitoring data for each region.